The world bank's Africa action plan: new actions? - Helmut Asche (Deutsches Institut für Entwicklungspolitik (DIE), 2006)
On request of its Executive Directors, the World Bank rolled out, in later summer 2005, how it envisages implementing decisions, in particular those taken in Gleneagles, on raising official development assistance (ODA) to Africa. The result is the Africa Action Plan (AAP) and, as of February 2006, the Africa Catalytic Growth Fund (ACGF). Building on a highly optimistic view of Africa's political and economic development, the Bank's aim is to strengthen the result and partner orientation of its work. In the undeclared competition among donor organizations, the Bank thus sees itself qualified for the role of administrator and coordinator alike, of a rising international development aid. The Bank points to its drivers-of-growth/shared-growth agenda as the most important innovation in the AAP. What is new about the agenda is, basically, the plan to scale up the Bank's infrastructure portfolio, which had been shrinking for decades. The Bank's economic diagnosis, self-assessment, and definition of sectoral priorities leave quite a number of critical questions for discussion.
Keywords: 330